A simple method for computing sprint acceleration kinetics from running velocity data: replication study with improved design - Morin, J.; Samozino, P.; Murata, M.; Cross, M.; Nagahara, R. (SportRxiv, 2019)
Measuring the ground reaction forces (GRF) underlying sprint acceleration is important to understanding the performance of such a common task, but until recently, direct measurements of GRF during sprinting were limited to only a few steps per trial. A simple method (SM) based on displacement- or velocity-time data fitted by an exponential model and basic computations applied to the runner`s center of mass was developed to estimate GRF across an entire sprint acceleration. The SM was validated against compiled force plate (FP) measurements, but because multiple-trials were required to generate a single acceleration profile fatigue and error may have introduced noise into the analyses. In this study, we replicated the original validation by comparing the main sprint kinetics and force-velocity-power variables (e.g. GRF and its horizontal and vertical components, mechanical power output, ratio of horizontal component to resultant GRF) between synchronized FP data and SM data derived from running velocity measured with a 100 Hz laser. This was made possible thanks to a newly developed 50 m FP system providing seamless GRF data during a single sprint acceleration. 16 trained male sprinters performed 2 all-out 60-m sprints. We observed good agreement between the two methods for kinetic variables (e.g. grand average absolute bias of 4.08%, range 0.692 0.536 - 6.33 3.45%), and high inter-trial reliability (grand average standard error of measurement of 2.50% for FP and 2.36% for the SM). This replication study clearly confirms the initial validation study: when implemented correctly, this method accurately estimates sprint acceleration kinetics.